ANALISIS TERJADINYA PERGESERAN NILAI ADAT PERNIKAHAN PADA MASYARAKAT SUKU KARO DI DESA PURWOBINANGUN - Rasenda; Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Karo wedding customs and analyze the causes of the shift in traditional values in the Karo community in Purwobinangun Village, Langkat Regency. The study used a qualitative method with a phenomenological approach. The research informants consisted of four people consisting of one traditional leader, two couples who had carried out Karo traditional weddings, and one community member who understood Karo wedding customs. Data were obtained through observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the community still maintains the main stages of Karo wedding customs and the Rakut Sitelu kinship system, but the implementation has been simplified, such as the combination of procession stages, reduced family involvement, and increased use of outside services in organizing traditional celebrations. The shift in values is also evident in the changing interpretation of customs by the younger generation, who emphasize practical aspects over philosophical meaning. Factors contributing to this shift include economic conditions, education levels, modernization, technological developments and social media, and changes in societal mindsets. Nevertheless, the values of family, mutual cooperation, and respect for customs remain as the cultural identity of the Karo people. This research demonstrates the importance of community education and traditional leaders in strengthening the transmission of cultural values to ensure their relevance to current developments without diminishing the noble values of Karo customs.